Microwave-assisted solvent free efficient synthesis of 1,3,4-oxadiazole-2(3H)-thiones and their potent in vitro urease inhibition activity - Shahzad, Sohail Anjum; Yar, Muhammad; Khan, Zulfiqar Ali; Khan, Islam Ullah; Naqvi, Syed Ali Raza; Mahmood, Nasir; Khan, Khalid Mohammed (European Journal of Chemistry, 2012)
An efficient solvent free microwave assisted synthesis of 5-substituted-1,3,4-oxadiazole-2(3H)-thiones (2a-2r) from hydrazides and carbon disulfide has been accomplished in good to excellent yield. The urease inhibition activity of the resulting compounds was investigated. Preliminary bioassay indicated that the compound 2j bearing 2-bromo substituent is the most active inhibitor exhibiting IC50 12.60 ± 0.92 μM.